A remarkable chaotic analysis for coherence fraction order with its applications. (January 2022) - Bary, Ghulam; Ahmed, Waqar; Sajid, Muhammad; Ahmad, Riaz; Alshammari, Nawa; Khan, Ilyas
Abstract: Multi-particle quantum statistical correlations measured in the collisions of heavy nuclei at the unrivaled energies. Remarkable consequences have been observed and speculated that such significant repercussions may arise due to non-chaotic and granular nature particle emanated sources. To study such kind of chaotic fraction as well as the particles emission, we have demonstrated and analyzed the ejection of particles from the disseminated agglomeration of tiny droplets which produced quantum statistics multi-particle correlations which do not only reflect the size of the fluid droplets but also contribute the specific clues about the congenital properties of chaos-coherence matter produced during the collisions. Such correlations possess the existence of gesture of the mixed-phase of chaotic and coherent fractions in the considered collisions. The main object of this research is that we investigate the intrinsic properties of produced matter by intensity correlations to utilize it in engineering applications. The purpose of these findings is to analyze the meticulous correlations to expedite the nature of the particle ejecting sources and observe remarkable suppression in the cumulant correlations relative to the full three and four particles interferences in the granular nature sources.